S91 Remote monitored physical activity is related to established measures of clinical risk in patients with pulmonary arterial hypertension. (11th November 2022) - Patel, J; Middleton, J; Battersby, C; Zafar, H; Binmahfooz, S; Neelam-Naganathan, D; Toshner, M; Reddy, A; Lewis, R; Watson, L; Swift, A; Condliffe, R; et al.
Abstract : Background: In patients with pulmonary arterial hypertension (PAH), hospital-based field walk testing is used as a clinical study endpoint and to estimate risk and guide treatment. The relationships between indicators of clinical risk and remote monitored physical activity is unknown. Here we report the relationship between baseline parameters that indicate clinical risk and remote monitored cardiac and physical activity measures. Methods: 80 patients were recruited to the arrhythmia sub-study of the United Kingdom National cohort study of Heritable and Idiopathic PAH (NCT01907295 ), and implanted with an insertable cardiac monitor (LinQ, Medtronic) and remote monitoring established through a regulatory approved system. Daily physical activity, heart rate, and heart rate variability was related to baseline World Health Organisation functional class (WHO-FC); N-terminal-Pro B-type natriuretic peptide (NTProBNP) and COMPERA 2.0 risk score. Results: Daily physical activity was reduced with a high WHO-FC (WHO-FC 1 vrs 3&4, P<0.001, figure 1 ), increased NTProBNP (P<0.001), and increased COMPERA 2.0 risk score (P<0.001), and correlated with incremental shuttle walktest (p<0.01). Indicators of cardiopulmonary function including heart rate variability and night heart rate were also related to WHO-FC, NTproBNP and COMPERA 2.0 risk (P<0.01). Conclusion: Daily, remote measured physical activity, heart rate variability, and night heart rate are related to established measures of clinical risk in patients with PAH.